Effectiveness of Online Teaching & Learning during Covid-19 Pandemic - Social Studies Students’ Perspective - Qolamani, Khalid (Humanities Journal of University of Zakho, 2022)
This study aimed to identify the Effectiveness of Online Teaching & Learning during Covid-19 Pandemic - Social Studies Students’ Perspective at Zakho University on the impact of the following variables (Gender, Study stage). The sample included (217) Social Studies Students, A questionnaire of 20 items was adapted by Wickramasinghe (2021) and distributed to the research sample, and the study reached the results that there are no statistically significant differences at the level of significance (α ≤ 0.05) between the averages responses of the study sample members attributed to the variable (Gender, Study stage). That means is an effect and benefit for Online Teaching & Learning During Covid-19 Pandemic - Social Studies Students’ Perspective regarding the two study variables (gender and study stage), and there is no effect of this process regarding the interaction between gender and study stage. Based on the results of this study, the researcher recommended that most important of which is the necessity of providing software by the university presidency to suit all business and all academic levels, the need to find a mechanism in distances learning that seeks to develop students’ practical skills.